Chapter 2.1 A Novel Definition of Professional Staff - Stefan de Jong (Emerald Publishing Limited, 2023)
Based on a review of professional staff (PS), which includes research managers and administrators, in 54 academic publications, I propose a novel definition for this category of staff: `degree holding university employees who are primarily responsible for developing, maintaining and changing the social, digital and physical infrastructures that enable education, research and knowledge exchange'. The proposed definition facilitates the development of new research questions that target the level of the organisational fields of higher education and science, to complement research on the university and individual levels. This view supports the study of the contributions of PS to higher education and science. I anticipate that such a broader focus will help to counter and nuance accounts of `administrative bloat' by focusing on how PS as a group shape and are shaped by the organisational fields of higher education and science, rather than dismissing them as superfluous or parasitic.
10.1108/978-1-80382-701-820231010; 10.1108/978-1-80382-701-820231010; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262